ADJUSTMENT OF HOUSES IN KAMPUNG INGGRIS DURING THE PANDEMIC SITUATION - Devi Adillah Nuraini; Ardhya Nareswari (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2023)
Coronavirus disease has implications for changes to home arrangements. Kampung Inggris is an educational village in Tulungrejo Village and Palem Village, Pare, Kediri, East Java that offers language learning activities. There are at least 60 course institutions that are active during the COVID pandemic. In terms of architecture, the course institution building is a residential house that has been developed into a house for residence and business, showing the use of dual functions. Changes or adjustments to the house are made so as not to limit daily activities in the house with a dual function as a residence with an educational course business function during the COVID-19 pandemic. This study aims to reveal the various changes in business housing that were carried out during the Covid-19 pandemic. The research was conducted using qualitative research methods to describe changes in depth. The variety of changes was analyzed by making a typology of the types of changes that occurred. The results showed that the most common changes found were the changes in space elements. They are, firstly, interior-element changes by dividing the space using semi-fixed elements made of wood planks for restroom needs. The second is outdoor-element changes by adding furniture for other business activities and study rooms in the form of chairs and tables.